Water Purification Efforts and the Black-White Infant Mortality Gap, 1906-1938 - D. Mark Anderson; Kerwin Kofi Charles; Daniel I. Rees; Tianyi Wang (Institute of Labor Economics (IZA), 2019)
According to Troesken (2004), efforts to purify municipal water supplies at the turn of the 20th century dramatically improved the relative health of blacks. There is, however, little empirical evidence to support the Troesken hypothesis. Using city-level data published by the U.S. Bureau of the Census for the period 1906-1938, we explore the relationship between water purification efforts and the black-white infant mortality gap. Our results suggest that, while water filtration was effective across the board, adding chlorine to the water supply reduced mortality only among black infants. Specifically, chlorination is associated with an 11 percent reduction in black infant mortality and a 13 percent reduction in the black-white infant mortality gap. We also find that chlorination led to a substantial reduction in the black-white diarrhea mortality gap among children under the age of 2, although this estimate is measured with less precision.
Keywords: I18; J11; J15; N3; 330; infant mortality; public health; black-white infant mortality gap